Implementation of Character Building in Cultivating Student Respect through Classical Guidance Services at SMPIT Ibnu Khaldun - Nabilaa Faizatuz Zuhriyah; Nina Siti Marlina; Jajat Darojat (Publikasi Indonesia, 2025)
The low level of respect among students towards teachers, peers, and the school environment is a challenge in character building in the digital era. This study aims to analyze the Implementation of Character Building in Cultivating Student Respect through Classical Guidance Services at SMPIT Ibnu Khaldun. The study used a qualitative method with a case study approach. Data collection techniques were carried out through observation, in-depth interviews with guidance counselors, principals, and students, as well as documentation. Data analysis using the Miles and Huberman model included data reduction, data presentation, and drawing conclusions. The results of the study showed that the implementation of respect character building was carried out through three stages: (1) planning by integrating Islamic values and respectful character in the RPL of classical guidance; (2) implementation using interactive group discussions, role-playing, and storytelling methods; (3) evaluation through behavioral observation and student self-assessment. Supporting factors included the commitment of guidance counselors, support from school management, and Islamic culture. Obstacles in the form of heterogeneity of student character and limited time were overcome through collaboration with homeroom teachers. The implications of this study provide a practical model for Islamic schools in optimizing classical guidance services for the formation of respectful character in students.